2019
DOI: 10.1177/1687814019895742
|View full text |Cite
|
Sign up to set email alerts
|

Influence of capsule length and width on heat transfer in capsule-type plate heat exchangers

Abstract: Capsule-type plate heat exchanger has the advantages of less deposition and low flow resistance. Based on previous research, numerical studies of capsule-type plate heat exchangers with different capsule lengths and widths for the Reynolds number ranging from 600 to 10,000 are performed. The results show that wake vortices, transverse vortices, and longitudinal vortices generate in the channels by the flow shearing and separation. The vortices promote the swirl and flow destabilization, exchange the fluid betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Furthermore, at the backside of the conical stamping, the heat transfer coefficient is low owing to flow stagnation and separation of the wake region. The same trends are shown by Jiang et al [12].…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, at the backside of the conical stamping, the heat transfer coefficient is low owing to flow stagnation and separation of the wake region. The same trends are shown by Jiang et al [12].…”
Section: Resultssupporting
confidence: 87%
“…However, the liquid in this case warms more intensively in the middle of the stream. This can be explained by observing that longitudinal vortices are formed, which increase heat transfer [12]. The structure of the vortex system is strongly influenced by the channel Fluids between plates move along clearly defined trajectories.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two different performance evaluations have been conducted to evaluate the comprehensive characteristics of capsule-type plate heat exchangers. It is concluded that such heat exchangers with small length and diameter parameters are recommended for use with the intensive heat transfer of the flow [2].…”
Section: Literature Review On the Issue 21 Design Solutions Of Heat E...mentioning
confidence: 99%
“…Since the length of the holding tube represents the pasteurization time, it is very important to calculate it accurately and correctly. The holding time of raw milk at 72 o C temperature during pasteurization should not be less than 16 seconds [10,11]. It is important to accurately calculate the duration of holding in the case where the power of the pasteurizer and the inner diameter of the selected zig-zag tube are clear.…”
Section: Introductionmentioning
confidence: 99%